The Beatles anthology. 5 & 6 [videorecording (DVD)] - Lennon, John, 1940-1980; McCartney, Paul; Harrison, George, 1943-2001; Starr, Ringo; Wonfor, George (Apple Corps Ltd. ; Capitol Records, 2003)
A visual history of the Beatles. Includes their songs, successes and failures.